2019
DOI: 10.1080/24750263.2018.1540669
|View full text |Cite
|
Sign up to set email alerts
|

High level of genetic variation in mitochondrial 16S rDNA among populations of Porcellionides pruinosus (Brandt, 1833) (Crustacea: Isopoda: Oniscidea) in Tunisia

Abstract: For more than 20 years, the cosmopolitan species Porcellionides pruinosus (Brandt, 1833) has been characterised by a controversial taxonomic status. This "species" has a high ecological plasticity, which enabled it to conquer different kinds of habitats. Besides that, this "species" exhibits a geographical variation in its morphological features and its reproduction pattern. In fact, some Tunisian populations had a seasonal reproductive period and while others showed a reproductive activity. A genetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Pairwise genetic distances among Porcellionides pruinosus populations, in our present study, ranged from 0.000 to 0.002. This closely genetic relation was consistent with the findings of Delhoumi et al [14] , who reported that the lowest genetic distances among populations of Porcellionides pruinosus in Tunisia, was found among Sbiba, Elfeija, Monastir, Chebba, and Sned.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Pairwise genetic distances among Porcellionides pruinosus populations, in our present study, ranged from 0.000 to 0.002. This closely genetic relation was consistent with the findings of Delhoumi et al [14] , who reported that the lowest genetic distances among populations of Porcellionides pruinosus in Tunisia, was found among Sbiba, Elfeija, Monastir, Chebba, and Sned.…”
Section: Discussionsupporting
confidence: 92%
“…The global species Porcellionides pruinosus (Brandt, 1833) display geographical diversity of its morphological characteristics and its reproduction pattern. In addition, it has a dialectical taxonomic history and wide ecological plasticity [14] . Pairwise genetic distances among Porcellionides pruinosus populations, in our present study, ranged from 0.000 to 0.002.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the low divergence levels between COI sequences reported herein may be the result of infection with Wolbachia. Infection with this endosymbiotic bacterium has been proposed to reduce mitochondrial polymorphisms in arthropods, including isopods (Marcadé et al 2009;Xiao et al 2012;Delhoumi et al 2019; but see Tang et al 2019). We cannot determine whether Wolbachia have reduced mitochondrial diversity in T. maindroni in the Persian Gulf as we did not test for the presence of Wolbachia in our specimens.…”
Section: Discussionmentioning
confidence: 90%
“…This species was used in bioremediation tests like pesticides degradation (Loureiro et al 2002) and as a bioindicator species of soil contamination (Loureiro et al 2005(Loureiro et al , 2009. In addition, many investigations were realized using genetic (Grandjean et al 2005;Delhoumi et al 2019a) and biochemical approaches (Achouri et al 2012) to study the interpopulation polymorphism of P. pruinosus. Despite this, little is known about the gut microbiota structure, dynamic and role within this species.…”
Section: Introductionmentioning
confidence: 99%